Effects of Bacillus coagulans TBC169 on gut microbiota and metabolites in gynecological laparoscopy patients - Gao, Weiqi; Yan, Ya; Guan, Zhaobo; Zhang, Jingmin; Chen, Weihong (Frontiers in Microbiology, 2024)
Objective: The primary objective of this study is to investigate the mechanism by which Bacillus coagulans TBC169 accelerates intestinal function recovery in patients who have undergone gynecological laparoscopic surgery, using metabolomics and gut microbiota analysis.Methods: A total of 20 subjects were selected and randomly divided into two groups: the intervention group (n=10) receiving Bacillus coagulans TBC169 Tablets (6 pills, 1.05×10 8 CFU), and the control group (n=10) receiving placebos (6 pills). After the initial postoperative defecation, fecal samples were collected from each subject to analyze their gut microbiota and metabolic profiles by high-throughput 16S rRNA gene sequencing analysis and untargeted metabonomic analysis methods.Results: There were no statistically significant differences observed in the α-diversity and β-diversity between the two groups; however, in the intervention group, there was a significant reduction in the relative abundance of unclassified_Enterobacteriaceae at the genus level. Furthermore, the control group showed increased levels of Holdemanella and Enterobacter, whereas the intervention group exhibited elevated levels of Intestinimonas. And administration of Bacillus coagulans TBC169 led to variations in 2 metabolic pathways: D-glutamine and D-glutamate metabolism, and arginine biosynthesis.This study demonstrated that consuming Bacillus coagulans TBC169 after gynecological laparoscopic surgery might inhibit the proliferation of harmful Enterobacteriaceae; mainly influence 2 pathways including D-glutamine and D-glutamate metabolism, and arginine biosynthesis; and regulate metabolites related to immunity and intestinal motility; which can help regulate immune function, maintain intestinal balance, promote intestinal peristalsis, and thus accelerate the recovery of intestinal function.